FGF-23 Levels before and after Renal Transplantation - Domniki Economidou; Spyros Dovas; Aikaterini Papagianni; Panagiotis Pateinakis; Dimitrios Memmos (Journal of Transplantation)
Phosphatonin fibroblast growth factor-23 (FGF-23) is involved in phosphate (P) excretion and vitamin D metabolism. Recently, FGF-23 has been suggested to be responsible for the hypophosphatemia and inappropriately low calcitriol levels observed after renal transplantation. We performed a prospective study to investigate FGF-23 levels in patients with end-stage renal disease before and after renal transplantation and their probable association with markers of bone and mineral metabolism. Intact FGF-23 levels were determined before and at 3, 6, and 12 months posttransplantation in 18 renal transplant recipients. Intact parathyroid hormone (iPTH), calcium (Ca), P, 25(OH)VitD, and 1,25(OH)2VitD levels were measured at the same time periods. Renal threshold phosphate concentration (TmPO4/GFR) was also calculated at 3, 6, and 12 months posttransplantation. The results showed that FGF-23 levels decreased by 89% 3 months posttransplantation (346 ± 146 versus 37 ± 9 pg/mL, 𝑃<.01) and remained stable throughout the study period. iPTH and P levels also decreased significantly after renal transplantation, while Ca and 1,25(OH)2VitD increased. Pretransplantation FGF-23 was significantly correlated with P levels at 3 months posttransplantation (𝑃<.005). In conclusion, FGF-23 levels decrease dramatically after successful renal transplantation. Pre-transplantation FGF-23 correlate with P levels 3 months posttransplantation.